Does altitude have an effect on stroke mortality and hospitalization risk? A comprehensive evaluation of United States data - Gerken, Jacob; Huber, Nathan; Zapata, Demi; Barron, Ileana G.; Zapata, Isain (Frontiers in Stroke, 2023)
Background Globally, stroke is a leading cause of death among people over 50 years of age. In the United States alone, over 150,000 people die due to stroke every year. Environmental factors such as altitude may play a role in these outcomes; however, their effects have not yet been comprehensively explored. The objective of this study is to evaluate the effect of altitude along with other covariates on stroke mortality and hospitalization rates in adults. Methods This study utilized altitude, stroke mortality and hospitalization rates; antihypertensive and cholesterol-lowering medication usage; smoking prevalence; and sociodemographic data (MH-SVI) obtained from government databases for 3,141 counties in the United States from 2018 to 2020. Data were analyzed using generalized additive models with and without adjustments for covariates. Results Unadjusted models show that altitude has a comparable significant negative effect on mortality rates for Black and white populations. When including all covariates, altitude continues to have a significant protective effect against stroke fatalities in white populations (retaining 26.6 and 53.8% of the effect magnitude for cardiovascular disease (CVD) and stroke mortality, respectively), a non-significant effect in the Black population, and a detrimental effect in Hispanic and Asian Pacific populations for CVD mortality (a 21.6 and 39.1% effect increase, respectively). Conclusion Our findings add to the growing body of evidence that environmental factors add to disparities between racial groups and play a significant role in CVD and stroke mortality. The effect of altitude is comparable in size to that of smoking, medication usage, and social determinants of health.